Рrofessional skills of live broadcast (Herald of Journalism, 2020)
The article focuses on the challenges that broadcast media face, par- ticularly in interactivity and live broadcast. Work in a broadcasting live is required from journalist a lot of creativity skills and professional experi- ence. Broadcasting live has a lot of features and a journalist working in a live broadcast should take into account all these nuances.
Keywords: live, linguistic and psychological aspects of live, chrono- logical time setting, target audience, competitive personnel, professional competence leading, professional level live.